Development of Nutrition Education Media in the Form of Booklets on the Importance of Breakfast for Junior High School Students - Widi Nur Aisyah; Luluk Ria Rakhma (Publikasi Indonesia, 2024)
Educational media has an important role in students' learning process. The number of student score results has decreased, indicating that students' understanding of the material is relatively low. Media that feels appropriate and in accordance with current conditions is booklet learning media. The purpose of this study was to analyze the understanding of junior high school students using booklet learning media. This research uses Research and Development research procedures (research and development). The analysis of this study is a questionnaire on the feasibility of educational media through booklets. The questionnaires tested the validity of media experts and material experts and student learning outcomes with the existence of learning media through booklets.